Identification of avian influenza virus of Indonesian isolates by reverse transcriptase polymerase chain reaction (RT-PCR) method - N.L.P.I. Dharmayanti; R Damayanti; A Wiyono; R Indriani; Darminto . (Indonesian Center for Animal Research and Development (ICARD), 2004)
An outbreak of avian influenza in Indonesia was reported at the first time at the beginning of September 2003 causing high mortality among poultry population especially commercial layer chicken farms in Java, Sumatra and Bali islands. From the outbreaks highly pathogenic avian infuenza viruses have been isolated and characterized by rapid, HA, HI and AGP tests. However, these isolates are still needed to be further molecularly characterized. The aim of this study is to identify by further subtyping the avian viruses by means of RT-PCR using Matrix, H7 and H5 primers. The study reveals that the RT-PCR using Matrix primer amplified a 200-300 basepairs (bp) Jawa Timur isolates were collected from East Java, while Jawa Barat isolates were from West Java. The RT-PCR using H7 primers did not amplify any product, while H5 primer amplified a 500-600 bp product from the isolates. It is concluded that the outbreak of poultry disease in East and West Java was caused by an avian influenza H5 subtype. Key words: Identification, avian influenza virus, RT-PCR, H5 subtype